Construct Validation of Science Literacy Instrument with Rasch Modeling on Students of Grade VIII Junior High School - Tabacholly, Fahriana Alfiokti; Susongko, Purwo; Nafiati, Dewi Amaliah (Journal of English Language and Education, 2025)
This study aims to develop and analyze science literacy assessment instruments for grade VIII junior high school students using Rasch modeling. The development and analysis of the instrument was carried out with an approach that includes content, substantive, structural, and consequential aspects. The science literacy assessment instrument was developed based on eight science learning materials for grade VIII semester 1, designed to represent science literacy competencies according to PISA standards, namely: explaining phenomena scientifically, interpreting data and evidence scientifically, and evaluating and designing scientific enquiry. The questions are presented in the form of multiple choice with a total of 48 itemsThis study used the Research and Development (RD) method with Tessmer's Formative Research design. The research approach applied is mixed methods, which combines qualitative and quantitative approaches. Research data were obtained from 158 students at SMPN 7 Brebes. The results of data analysis using the Rasch model with the R version 4.4.2 program and the eRm package showed that 85% of the items were valid with a p value 0.01. Based on validation covering content, psychometric, and construct aspects (consisting of content, substantive, structural, and external), this instrument meets the requirements as a good quality item